2016
DOI: 10.1242/bio.017608
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TC-1 enhances radiosensitivity of non-small cell lung cancer via the Wnt/β-catenin pathway

Abstract: Thyroid cancer 1 (TC-1, C8ofr4) is widely expressed in vertebrates and associated with many kinds of tumors. Previous studies indicated that TC-1 functions as a positive regulator in the Wnt/β-catenin signaling pathway in non-small cell lung cancer (NSCLC). However, its exact role and regulation mechanism in radiosensitivity of NSCLC are still unclear. The expression level of TC-1 was measured by qRT-PCR and western blot in NSCLC cell lines. Proliferation and apoptosis of NSCLC cells in response to TC-1 knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…and EMT in NSCLC via regulating WNT/b-catenin signal [48]. Wu et al revealed that knockdown of TC-1 promoted the susceptibility of NSCLC cells to radiosensitivity via the Wnt/ b-catenin signal [49]. Furthermore, aberrant expression of Wnt1/b-Catenin is considered as an independent poor prognostic marker of NSCLC after surgery [50].…”
Section: Discussionmentioning
confidence: 99%
“…and EMT in NSCLC via regulating WNT/b-catenin signal [48]. Wu et al revealed that knockdown of TC-1 promoted the susceptibility of NSCLC cells to radiosensitivity via the Wnt/ b-catenin signal [49]. Furthermore, aberrant expression of Wnt1/b-Catenin is considered as an independent poor prognostic marker of NSCLC after surgery [50].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway is an important signaling pathway involved in the malignant progression of various tumors, and regulates the proliferation, migration and invasion of cancer cells (17)(18)(19). When Wnt is activated, β-catenin translocates from the cytoplasm to the nucleus and stimulates proto-oncogene cyclin D1 and c-Myc transcription (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that Wnt/β-catenin pathway may modulate the radiosensitivity of NSCLC cells. For example, knockdown of Thyroid cancer 1 sensitizes NSCLC cell lines to radiotherapy through the Wnt/β-catenin signaling pathway (Wu et al, 2016). In addition, GDK-10017, an inhibitor of the Wnt/ β-catenin signaling pathway, causes significant radiosensitivity of NSCLC cells (Wickham et al, 1997).…”
Section: Introductionmentioning
confidence: 99%